Targeting Signaling Pathway Networks in Several Malignant Tumors: Progresses and Challenges - He, Hongdan; Shao, Xiaoni; Li, Yanan; Gihu, Ribu; Xie, Haochen; Zhou, Junfu; Yan, Hengxiu (Frontiers in Pharmacology, 2021)
Malignant tumors remain the health problem of highest concern among people worldwide due to its high mortality and recurrence. Lung, gastric, liver, colon, and breast cancers are among the top five malignant tumors in terms of morbidity and mortality. In cancer biology, aberrant signaling pathway regulation is a prevalent theme that drives the generation, metastasis, invasion, and other processes of all malignant tumors. Based on previous research, we concluded that the secretory glycoprotein/β-serial protein, phosphatidylinositol-3-kinase/protein kinase B/mammalian rapamycin target protein, Notch, and nuclear factor kappa beta signaling pathways are the most frequently dysregulated pathways in malignant tumors. This review provides an innovative summary of the recent progress in research on these signaling pathways, the underlying mechanism of the molecules involved in these pathways, and the important role of some miRNAs in tumor-related signaling pathways. It also presents a brief review of the antitumor molecular drugs that target these signaling pathways. This review may provide a theoretical basis for the study of the molecular biological mechanism of malignant tumors and vital information for the development of new treatment strategies with a focus on efficacy and the reduction of side effects.